Age Related Neurodegenerative Disorders w.s.r to Dementia (International Journal of Ayurveda and Pharma Research, 2022)
Aging can be defined as the gradual anatomical and physiological decline which begins to after the achievement of sexual maturity. Vriddhavastha (senility) is Vata dosha prominent phase of life. Gunas (qualities) of Vata dosha are degenerative by the nature which is increased; they result in degenerative changes in the body in terms of Dhatukshaya, Ojakshaya and Balakshaya which result in Neuro degeneration. Dementia is the progressive deterioration of intellect, emotional control, behavior and motivation along with loss of memory. Vriddhavastha (aging) is Vata dosha prominent Avastha. Vata has some Guna (qualities) that get involved in the degenerative process in the body like Laghu guna and Khara guna which is act as Lekhaniya (scraping), Vishada guna has Kshalanashakti (elution power) and, Ruksha guna has Shoshanashakti (absorbability), etc. With increasing Vata dosha, these above Gunas are also be increased, might be together or separately and will initiate the process of degeneration in the body in the terms of Dhatukshaya, Ojakshaya and Balakshaya causing various degenerative diseases. Dementia is one among them. Symptomatology of dementia are similar to Vata vriddhi lakshana, Vata nanatmajavyadhi and Ojakshaya lakshana. Manifestation of the disease condition is purely due to degenerative changes in senile periods. The disease condition is not a reversible but with the healthy changes in dietary habits and lifestyle, the disease condition might be preventable and delayed.